(untitled) (Revista Argentina de Musicología, 2018)
Arbol is an Argentine alternative rack group that combines styles of hardcore, rap. funk. reggae and local folk roots. We analyze the esthetic intercrossing the group proposes in its second work, entitled Chapusongs, produced by Gustavo Sataolalla and Surco-Universal. The group has established its esthetic identity by means of multiple styles and genres, reaching its own peculiar expression. This work tries to approach the complex and varied reception of rack as a genre. movement and identity expression of the urban youth culture. We show, on one hand, how Arbol builds up its identity avoiding the being pigeonholed in only one genre or style. On the other hand. this is one more case when musicians of different formation have adopted the rock matrix lo reach out to other genres, progressively attaining a scope encompassing all music.